Kewenangan dan Tanggung Jawab Tim Investigasi Dalam Pengawasan Dan Pembinaan Notaris - Setiadewi, Kadek; Rudy, Dewa Gde (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 03 (2021), 2021)
Abstract This paper aims to examine the authority of the Investigation Team in the supervision and guidance of Notaries and also to find out the responsibilities of the Investigation Team regarding the supervision and guidance of Notaries. The writing of this article uses a normative legal research method and uses a statutory approach and a conceptual approach. The results of this research are that referring to the Decree of the Ministry of Law and Human Rights Number: AHU03.UM.01.01 of 2018, the investigation team has several powers, namely receiving public complaints that are directly submitted to the regional office, helping the smooth work of the Notary Supervisory Council, and also examining complaints received. Meanwhile, the responsibility of the Investigation Team is to find a bright spot on the problems faced by the Notary in a report on violations of the Law on the Position of Notary that is reported by the public.   Abstrak Tulisan ini bertujuan untuk mengkaji k ewenangan dari Tim Investigasi dalam pengawasan dan pembinaan Notari s dan juga untuk mengetahui tanggung jawab dari Tim Investigasi terkait dengan pengawasan dan pembinaan Notaris . Penulisan artikel ini menggunakan metode penelitian hukum normatif dan mengunakan pendekatan perundang–undangan dan pendekatan konseptual. Adapun hasil dari penelitian ini adalah bahwa merujuk SK Kemenkumham Nomor: AHU03.UM.01.01 Tahun 2018, tim investigasi memiliki beberapa kewenangan yaitu menerima pengaduan masyarakat yang langsung disampaikan kepada kantor wilayah, membantu kelancaran tugas daripada Majelis Pengawas Notaris, dan juga memeriksa pengaduan yang diterima, sedangkan tanggung jawab dari tim investigasi adalah mencari titik terang dari permasalahan yang dihadapi Notaris dalam suatu laporan pelanggaran Undang-Undang Jabatan Notaris yang dilaporkan oleh masyarakat.